2003
DOI: 10.1088/0953-4075/36/17/104
|View full text |Cite
|
Sign up to set email alerts
|

Saturated multikilovolt x-ray amplification with Xe clusters: single-pulse observation of Xe(L) spectral hole burning

Abstract: Single-pulse measurements of spectral hole burning of Xe(L) 3d → 2p hollow atom transition arrays observed from a self-trapped plasma channel provide new information on the dynamics of saturated amplification in the λ ∼ 2.8-2.9 Å region. The spectral hole burning on transitions in the Xe 34+ and Xe 35+ arrays reaches full suppression of the spontaneous emission and presents a corresponding width hω x ∼ = 60 eV, a value adequate for efficient amplification of multikilovolt x-ray pulses down to a limiting length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 13 publications
11
80
0
Order By: Relevance
“…(1) correspond to the pulse width zX e 100 as, we note that the observation [7] of single-pulse spectral hole-burning on the Xe(L) system at h -2.85 A with a width Ah% -60 eV, a value that corresponds to a temporal duration of z , -30 as,…”
Section: T 3 -3mentioning
confidence: 75%
See 1 more Smart Citation
“…(1) correspond to the pulse width zX e 100 as, we note that the observation [7] of single-pulse spectral hole-burning on the Xe(L) system at h -2.85 A with a width Ah% -60 eV, a value that corresponds to a temporal duration of z , -30 as,…”
Section: T 3 -3mentioning
confidence: 75%
“…The recent observation [6,7] of strong amplification on Xe(L) hollow atom transitions in the multikilovolt spectral region (-4400 eV) at h, -2.71-2.93 8, introduces the possibility of extending the generation of such stable highly confined ordered modes of deeply penetrating propagation to x-ray wavelengths in materials at solid density. The importance and abundance of water, in either liquid or solid form, nominate it as a leading system for study.…”
Section: ) Multikilovolt Channeled X-rav Proaaaation In Watermentioning
confidence: 99%
“…This range corresponds physically to the development from raw manpower to rapid particle decay. The present status, roughly situated at 10 20 W/cm 3 , is experimentally associated with nuclear explosives, laser-induced nuclear fission [2,3,4], and coherent X-ray amplification [5,6]. An estimated, power density limit that could be achieved by the channeling of multikilovolt X-rays in a high-Z solid, designated as Ωα ∼ 10 30 − 10 31 W/cm 3 , is indicated the practical production of the power densities sufficient for amplification in the γ-ray region associated with nuclear transitions.…”
Section: History Of Power Compressionmentioning
confidence: 96%
“…[8]) observed in studies of multiple photoionization of noble-gas clusters by high intensity laser beam. In this studies a prominent amount of photons with energies of several hundreds eV were found signaling the possibility that vacancies in inner shells were generated during laser-cluster interaction.…”
Section: Effect On Multi-photon Ionizationmentioning
confidence: 98%
“…Indeed, the velocity υ in HF is not equal to i∇ . Instead, according to (8), one has in HF approximation…”
Section: Violation and Restoration Of The Gauge Invariancementioning
confidence: 99%